SARS‐CoV‐2 in human milk is inactivated by Holder pasteurisation but not cold storage. (7th August 2020) - Walker, Gregory J; Clifford, Vanessa; Bansal, Nidhi; Stella, Alberto O; Turville, Stuart; Stelzer‐Braid, Sacha; Klein, Laura D; Rawlinson, William
Abstract : Aim: As the COVID‐19 pandemic evolves, human milk banks world‐wide continue to provide donor human milk to vulnerable infants who lack access to mother's own milk. Under these circumstances, ensuring the safety of donor human milk is paramount, as the risk of vertical transmission of SARS‐CoV‐2 is not fully understood. Here, we investigate the inactivation of SARS‐CoV‐2 in human milk by pasteurisation and the stability of SARS‐CoV‐2 in human milk under cold storage. Methods: SARS‐CoV‐2 was experimentally inoculated into human milk samples from healthy donors or into a control medium. Triplicates of each sample were layered onto uninfected cells after Holder pasteurisation (63°C for 30 min), heating to 56°C for 30 min, or after 48 h of storage at 4°C or −30°C. Infectious titres of virus were determined at 72 h post‐infection by endpoint titration. Results: Following heating to 63°C or 56°C for 30 min, replication competent (i.e. live) SARS‐CoV‐2 was undetected in both human milk and the control medium. Cold storage of SARS‐CoV‐2 in human milk (either at 4°C or −30°C) did not significantly impact infectious viral load over a 48 h period. Conclusion: SARS‐CoV‐2 is effectively inactivated by Holder pasteurisation, suggesting that existing milk bank processes will effectively mitigate the risk of transmission of SARS‐COV‐2 to vulnerable infants through pasteurised donor human milk. The demonstrated stability of SARS‐CoV‐2 in refrigerated or frozen human milk may assist in the development of guidelines around safe expressing and storing of milk from COVID‐19 infected mothers.